Environment Matters at the World Bank, 2009 Annual Review : Banking on Biodiversity - World Bank (World Bank, 2012)
This issue of environment matters celebrates the 2010 international year of biodiversity and describes some of the challenges and opportunities in protecting biodiversity for the benefit of humankind. From the world's highest mountain ranges to the lowland plains, and from the great oceans and coastal wetlands to agricultural landscapes, nations and communities rely on the bounty and services of natural ecosystems. Biological resources and the goods and ecosystem services they provide underpin every aspect of human life and livelihoods, from food and water security to general well-being and spiritual fulfillment. In many countries, it is the poorest of the poor who are most dependent on these benefits. Yet, as the Millennium Ecosystem Assessment showed, biodiversity is under severe threat, as ecosystems are being lost and degraded more rapidly and extensively than at any comparable period in our history. Habitat loss and fragmentation, overexploitation of resources, pollution, invasive alien species, and, increasingly, climate change will all lead to further biodiversity loss. One of the key challenges of the coming decades will be how to reconcile biodiversity conservation and development if we are to achieve the twin goals of poverty alleviation and a sustainable future for all. The World Bank is already a major global funder of biodiversity initiatives, including support to more than 624 projects in over 122 countries during the last 20 years. It is actively supporting national actions to safeguard biodiversity and improve natural resource management. Many of these projects have supported globally important protected areas, but efforts have also been made to mainstream biodiversity conservation in the production landscape. As well as national efforts, the Bank has supported numerous partnerships with international non-governmental organizations (NGOs) to promote global and regional biodiversity initiatives.